Karakteristik Usahatani dan Tingkat Literasi Keuangan Petani Swadaya di Desa Belangin Kecamatan Kapuas Kabupaten Sanggau - Sukirno; Yurisinthae, Erlinda; Kurniati, Dewi (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
Financial literacy helps independent smallholders make better financial decisions, while individual characteristics such as age, education, and experience affect financial literacy, which can improve the economic welfare of independent smallholders. Therefore, this study aimed to analyze the relationship between farming characteristics and the level of financial literacy in independent oil palm farmers. This study used a quantitative descriptive method. Primary and secondary data sources were analyzed using the Spearman rank test. The analysis results showed that education and land area had a significant positive relationship with the financial literacy of independent oil palm farmers, while age and farming experience had a significant negative relationship. Gender and number of dependents showed a weak and insignificant relationship. Education and larger land area tended to increase financial literacy, while age and experience did the opposite.